Internal Audit in Microfinance Institutions-Evidence from Transitional and Developing Economies - Omidiji A; Botica Redmayne N; Ehalaiye D; Gyapong E (John Wiley & Sons Ltd on behalf of European Bank for Reconstruction and Development., 2023)
Microfinance institutions (MFIs) are hybrid organisations that strive to balance business and social goals. This paper examines the determinants of the internal audit (IA) function in MFIs, with particular emphasis on the business goals, specifically efficiency, productivity, regulation and the gross portfolio yield. We also investigate whether the establishment of an IA function is associated with MFI's focus on their social objectives relating to outreach, and women director appointments. Multivariate regression results from 1025 MFIs across 63 countries show that MFIs' focus on their social objectives is related to their propensity to establish an IA function. Thus, outreach and women director appointments are positively related to the establishment of an IA function. Similarly, in terms of the performance emphasis, the gross portfolio yield (inefficiency) increases (decreases) the likelihood of establishing an IA, but productivity and regulation have no effect. The findings suggest that MFIs' dual focus on social and business objectives impacts the establishment of internal audits. The results are robust to various measurements and estimations.
Keywords: internal audit; microfinance; outreach; transitional economies; women directors